Decisions of Monetary Authorities in the Light of Monetary Policy Transparency - Noga, Marian (Decyzje władz monetarnych w świetle przejrzystości polityki monetarnej, 2009)
The analysis of the two approaches seems to favour collective decision-making as the approach that offers effective policy-making and the implementation of monetary decisions. The individual approach is, more often than not, charged with the burden of subjectivity since the policy-maker tends to form decisions based on individual value system and personal experience. Moreover, individual approach favours most obvious decisions, disregarding or neglecting alternative solutions to the problem at hand. By adopting the collective approach to decision-making, monetary authorities may augment the transparency of monetary policy in general, thus improving its efficiency and effectiveness.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 93-102
Keywords: strategy of direct inflation targeting (DIT); collective mind; individual approach to decision-making; cellective approach to decision-making